2021
DOI: 10.12659/msm.931471
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Lifestyle Habits of Chinese Plasma Donors: A Multicenter Study

Abstract: Background The demand for plasma and plasma products has increased in China, which has a short supply. Compared with whole blood donors, plasma donors and their donation behavior have received less attention. This study aimed to investigate the demographic characteristics and lifestyle habits of Chinese plasma donors. Material/Methods During 2018–2019, information on plasma donors was collected from blood product companies using a 25-item questionnaire, including sex, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Notably, the majority (60%) had a donation history of at least five years. 17 These data are quite different from those of US plasma donors.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Notably, the majority (60%) had a donation history of at least five years. 17 These data are quite different from those of US plasma donors.…”
Section: Discussionmentioning
confidence: 79%
“…16 There is an urgent need for countries outside of the US to attempt to increase their own source plasma production. 5,17 In addition, US plasma manufacturers must recover from the dramatic challenges of the COVID-19 pandemic. We believe that increased information regarding pre-pandemic donor demographics would help to serve as a baseline for evaluation of post-pandemic practices.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, about 30% of 18 to 30 year-old donors had detectable IgG, while about 60% of 50 year-old donors were seropositive ( Zaaijer, Koppelman & Farrington, 2004 ). A study in our laboratory on the characteristics of Chinese plasma donors showed that most plasma donors (78.5%) were aged 46–55 years old ( Sun et al, 2021 ). This may explain the prevalence of B19V-specific IgG in Chinese plasma donors.…”
Section: Discussionmentioning
confidence: 99%
“…China's plasmapheresis stations are primarily located in rural areas where the female population significantly outnumbers the male population, with female plasma donors outnumbering male donors by a factor of 2.4 [36]. Consequently, the majority of China's IVIG raw plasma is sourced from female donors.…”
Section: Introductionmentioning
confidence: 99%